The hills have eyes 2 - Craven, Wes.; Locke, Peter; Maddalena, Marianne; Craven, Jonathan; Weisz, Martin; McMillian, Michael, 1978-; Stroup, Jessica; Alonso, Daniella; Vargas, Jacob; Thompson Young, Lee, 1984-; Crowley, Ben.; Edelstein, Eric.; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2007)
Soldiers stop at a New Mexico outpost in order to deliver equipment to a group of atomic scientists. When they arrive at the isolated research camp, however, they find it mysteriously deserted. After spotting a distress signal in a distant mountain range, the team decides to embark on a search and rescue mission with the hope of locating the missing scientists. Little do they know that these are the very hills that the ill-fated Carter family once visited and that a tribe of cannibalistic mutants lies in wait. This time, there is an even larger force of evil at work. The family patriarch, Papa Hades, plans to keep the women as breeders in order to ensure the survival of the mutant clan. Thus, the inexperienced group of soldiers must learn to band together against a foe that is intent on their very destruction.
Title from container.
Based on the characters created by Wes Craven.
Director of photography, Sam McCurdy ; editors, Sue Blainey, Kirk M. Morri ; music, Trevor Morris ; costume designer, Katherine Jane Bryant ; production designer, Keith Wilson ; special effects supervisor, Jason Troughton ; visual effects supervisor, Jamison Scott Goei.
Michael McMillian, Jessica Stroup, Daniella Alonso, Jacob Vargas, Lee Thompson Young, Ben Crowley, Eric Edelstein, Flex Alexander, Reshad Strik, Michael Bailey Smith.
MPAA rating: R; for prolonged sequences of strong gruesome horror violence and gore, a rape and language.
DVD, region 1, widescreen (2.35:1) presentations; Dolby Digital 5.1 surround, Dolby surround.
Keywords: Soldiers -- New Mexico -- Drama; Scientists -- New Mexico -- Drama; Cannibalism -- New Mexico -- Drama; Search and rescue operations -- New Mexico -- Drama; Patriarchy -- New Mexico -- Drama; Feature films; Horror films; Thrillers (Motion pictures); Video recordings for the hearing impaired; French language materials; Spanish language materials; New Mexico -- Drama